PEMBERDAYAAN MASYARAKAT MELALUI USAHA EKONOMI DESA – SIMPAN PINJAM (UED-SP) SADUTI SEJAHTERA DI DESA LAMBANGSARI I, II, III KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU TAHUN 2015 - 2017 - Novia Shintia Dewi; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Community empowerment is a strategy in an attempt to achieve independence andwell-being of the community through a variety of development potential, especially in termsof economic development. With the development of village economy can accelerate povertyreduction. Rural community economic development can be realized through the RuralEconomic Enterprises Program - Savings and Loans (UED-SP) with the hope to improvepeople's lives and the economy of the village through saving and loans activities. Theproblems of this study (1) How to empower communities through UED-SP Saduti Sejahteraat Lambangsari I, II, III Village in 2015-2017? (2) The factors that influence the success ofUED-SP Saduti Sejahtera at Lambangsari I, II, III Village in 2015-2017?.The Purpose of This Reseacrh are (1) to Describe about community empowermentthrough the UED-SP Saduti Sejahtera at Lambangsari I, II, III Village in 2015-2017. (2) toKnowing the factors that influence the success of UED-SP Saduti Saduti Sejahtera atLambangsari I, II, III Village in 2015-2017. This research is a qualitative descriptiveapproach. The research data obtained from observation, interviews with sources, anddocumentation. From the results of this research is empowering society through UED-SPSaduti Sejahtera at Lambangsari I, II, III village includes several stages, (i) Possibility, thepreparation so that the preparation of the creation. (ii) Reinforcement, by conductingvarious training for program managers. (iii) Protection, measures to protect the activitiesof irregularities through the application of sanctions. (iv) Supporting, the form of on goingactivities to support UED-SP as through funds as well as the participation of members, and(v) Maintenance, to implement guidance and oversight through coordination meetings.UED-SP Saduti Sejahtera success at Lambangsari I, II, III village is influenced by severalfactors: communication made between all the parties concerned, resources and programimplementers applicable regulations.Keywords: Empowerment, Economy Village, UED-SP